Teaching the common core math standards with hands-on activities, grades K-2 - Muschla, Judith A.; Muschla, Gary Robert; Muschla-Berry, Erin (Jossey-Bass teacher., 2014)
"The new Common Core Math Standards have been formulated to provide students with instruction that will help them acquire a thorough knowledge of math at their grade level, which will enable them to move on to higher mathematics with competence and confidence. Along with learning concepts and skills, students need instruction and activities that encourage them to collaborate with other students, utilize technology, communicate ideas about math both orally and in writing, and gain an appreciation of the significance of mathematics to modern life. Hands-on Activities for Teaching the Common Core Math Standards, Grades K-2 is designed to address these needs. This resource has several important goals. The activities in this book will help students: Gain understanding of math concepts and skills, based on the new Common Core Standards, apply their understanding of concepts and skills, develop proficiency in calculations, learn to think abstractly, think critically using mathematical reasoning, employ various problem-solving strategies, gain fluency in communicating about math, develop the foundation for success in higher mathematics"--